Loss of fumarylacetoacetate hydrolase causes light‐dependent increases in protochlorophyllide and cell death in Arabidopsis. (12th March 2019) - Zhi, Tiantian; Zhou, Zhou; Qiu, Bo; Zhu, Qi; Xiong, Xingyao; Ren, Chunmei
Summary: Fumarylacetoacetate hydrolase (FAH) catalyses the final step of the tyrosine degradation pathway, which is essential to animals but was of unknown importance in plants until we found that mutation of Short‐day Sensitive Cell Death1 ( SSCD1 ), encoding Arabidopsis FAH, results in cell death under short‐day conditions. The sscd1 mutant accumulates succinylacetone (SUAC), an abnormal metabolite caused by loss of FAH. Succinylacetone is an inhibitor of δ‐aminolevulinic acid (ALA) dehydratase (ALAD), which is involved in chlorophyll (Chl) biosynthesis. In this study, we investigated whether sscd1 cell death is mediated by Chl biosynthesis and found that ALAD activity is repressed in sscd1 and that protochlorophyllide (Pchlide), an intermediate of Chl biosynthesis, accumulates at lower levels in etiolated sscd1 seedlings. However, it was interesting that Pchlide in sscd1 might increase after transfer from light to dark and that HEMA1 and CHLH are upregulated in the light–dark transition before Pchlide levels increased. Upon re‐illumination after Pchlide levels had increased, reactive oxygen species marker genes, including singlet oxygen‐induced genes, are upregulated, and the sscd1 cell death phenotype appears. In addition, Arabidopsis WT seedlings treated with SUAC mimic sscd1 in decline of ALAD activity and accumulation of Pchlide as well as cell death. These results demonstrate that increase in Pchlide causes cell death in sscd1 upon re‐illumination and suggest that a decline in the Pchlide pool due to inhibition of ALAD activity by SUAC impairs the repression of ALA synthesis from the light–dark transition by feedback control, resulting in activation of the Chl biosynthesis pathway and accumulation of Pchlide in the dark. Significance Statement: The role of the tyrosine degradation pathway in plants is not well understood. This study revealed a relation between the Tyr degradation pathway and the Chl biosynthetic pathway in mediating sscd1 cell death, which provides insight into the biological function of the Tyr degradation pathway in plants and the regulation of the Chl biosynthesis pathway and cell death.